2018
DOI: 10.3390/ijms19092517
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Graphene Oxide-Incorporated Polydimethylsiloxane Membrane with Hexagonal Micropillars

Abstract: Several efforts have been made on the development of bioscaffolds including the polydimethylsiloxane (PDMS) elastomer for supporting cell growth into stable sheets. However, PDMS has several disadvantages, such as intrinsic surface hydrophobicity and mechanical strength. Herein, we generated a novel PDMS-based biomimetic membrane by sequential modifications of the PMDS elastomer with graphene oxide (GO) and addition of a hexagonal micropillar structure at the bottom of the biomembrane. GO was initially homogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Graphene oxide (GO) has proven to be a promising nanocarrier in recent years, and has gained attention in many different fields [ 28 ]. Modified GO has been used in many pharmaceutical researches as a drug and gene delivery carrier, biosensor, and bioimaging agent [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Graphene oxide (GO) has proven to be a promising nanocarrier in recent years, and has gained attention in many different fields [ 28 ]. Modified GO has been used in many pharmaceutical researches as a drug and gene delivery carrier, biosensor, and bioimaging agent [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The serial passaging was used to select MSC-like cells which were more homogenous and exhibited pronounced fibroblast morphology. For the differentiation of iPSCs into iPSC-RPEs and iPSC-RGCs, the differentiation following the procedures reported by Regent et al [28], Yang et al [8] and the protocols for the routine generation of iPSC-RGCs in our laboratory [9,10] were used, respectively.…”
Section: Cell Culturementioning
confidence: 99%
“…Collectively, our data demonstrated that our proposed CNN model could be used for evaluating the differentiation degree of iPSC-derived cell lineages. To further verify the accuracy of iPSC-RPE image recognition by this proposed model, we picked up 6 dishes of iPSC-RPEs with various differentiation degree after undergoing the complete differentiation time course (Figure 9) using protocols reported by either Regent et al [28] or Yang et al [8] The differentiation degree of each iPSC-RPE dish was interpreted by qualified technicians after microscopic examination. Subsequently, the images of these cells were used as the input in the multi-slice tensor model and output using PCA.…”
Section: Evaluating the Differentiation Degree Of Ipsc-rpesmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface properties of the ECM have a strong influence on cell behaviors, such as adhesion, differentiation, and proliferation [6][7][8][9][10]. PDMS gained high popularity as a biocompatible material in the fabrication of devices for many biomedical applications, including the study of cellular communication, tissue engineering, and cell isolation [7,8,[11][12][13]. Its unique properties provide several advantages over other biocompatible and hydrophilic polymers.…”
Section: Introductionmentioning
confidence: 99%